Implementasi Perpustakaan Digital Berbasis Web untuk Meningkatkan Literasi Siswa di MAN 1 Jombang - Kurniawati, Putri; Junaris, Imam (Universitas Nusantara PGRI Kediri, 2025)
Digital transformation in the world of education requires madrasas to adapt to technological developments, one of which is through the implementation of digital libraries. This article discusses the implementation of a web-based digital library at MAN 1 Jombang with the aim of increasing student literacy while addressing various library management challenges. Activities are carried out by involving librarians, teachers and students in planning, implementation and evaluation. The results of the service show that the digital library provides easy access to collections via personal devices and increases student involvement in literacy activities. The challenges that arise are limited internet networks and the number of digital collections. The solutions taken include providing a more stable LAN network, regular collection updates, and involving students and teachers in determining collection needs. With this strategy, the digital library at MAN 1 Jombang is able to provide optimal services, strengthen literacy culture, and support technology-based learning. This activity shows that collaboration between stakeholders can strengthen the function of digital libraries not only as a collection provider, but also as a means of sustainable literacy development in the madrasah environment.